2017
DOI: 10.7166/28-4-1702
|View full text |Cite
|
Sign up to set email alerts
|

Leapfrogging to Renewable Energy: The Opportunity for Unmet Electricity Markets

Abstract: Electricity plays a crucial role in the socio-economic development of any country. Developing countries, however, unlike their developed counterparts, do not have electricity markets that are fully satisfied, nor are they 'laden' with large-scale infrastructure that could create inertia about making the transition. The objective of this paper is to identify the potential trajectories for unmet electricity markets in sub-Saharan Africa to leapfrog to renewable energy as they strive to accelerate access to elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Within energy transition work, a growing body of literature on energy communities has paid closer attention to the multi-dimensionality of household energy. However, most of these studies are shaped almost entirely by industrialized contexts and might not therefore be well suited for unmet energy markets [37]. In a review of 70 community energy studies, Klein and Coffey [38] found that most were done in industrialized countries in Europe, the United Kingdom (UK), United States and Australia.…”
Section: Co-designing Energy Solutionsmentioning
confidence: 99%
“…Within energy transition work, a growing body of literature on energy communities has paid closer attention to the multi-dimensionality of household energy. However, most of these studies are shaped almost entirely by industrialized contexts and might not therefore be well suited for unmet energy markets [37]. In a review of 70 community energy studies, Klein and Coffey [38] found that most were done in industrialized countries in Europe, the United Kingdom (UK), United States and Australia.…”
Section: Co-designing Energy Solutionsmentioning
confidence: 99%
“…As communities develop and are exposed to higher quality of life environments, communities generally become more self-controlled and population growths stabilise (ECSA 2019). An indication of population magnitudes is also given (after Bating et al 2017). Figure 2 gives an interesting synopsis of the current status quo with regard to energy supply and population demands on the African continent (Bating et al 2017, 32-49 A particular design approach in the new curriculum design was to include as much group work on the online My Unisa platform, and also strive to implantation of theory in a system or project design context.…”
Section: Some Opportunities As Available On the African Continentmentioning
confidence: 99%
“…Implementation of transition in the unmet electricity markets can therefore occur in two ways: from traditional to regime, or from regime to niche. However, the markets in the traditional energy arena can leapfrog to niche technologies (see Batinge et al, 2017) without going through regime technologies because of the low path-dependence due created by the lack of conventional energy infrastructure. We however acknowledge that political and socio-cultural norms can still serve as lock-ins, and inhibit leapfrogging.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%